2007
DOI: 10.1260/136943307781422226
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Calculation Approach of Torsionally Coupled Seismic Response for Base-Isolated Eccentric Structures

Abstract: More and more applications exist of base-isolated buildings. So far much attention has been paid to the improvement of design approaches. In this paper, the equation of motion is derived for a torsionally coupled base-isolated structure under the action of seismic ground motion. Based on numerical analyses of the structure, torsional responses and influencing parameters have been investigated and some rules obtained for sites with different soils, in which the superstructure is idealized as a series-rigid floo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Furthermore, Matsagar and Jangid (2005) investigated the effects of torsional coupling due to isolator parameters on the seismic response of base-isolated buildings. Li et al (2007) proposed a simplified calculation approach of the torsionally coupled seismic response for base-isolated eccentric structures. Mazza (2014) developed a computer code for the non-linear static analysis of spatial framed structures with an asymmetric plan based on arc-length methods.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Matsagar and Jangid (2005) investigated the effects of torsional coupling due to isolator parameters on the seismic response of base-isolated buildings. Li et al (2007) proposed a simplified calculation approach of the torsionally coupled seismic response for base-isolated eccentric structures. Mazza (2014) developed a computer code for the non-linear static analysis of spatial framed structures with an asymmetric plan based on arc-length methods.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2007) focused their studies on the torsional acceleration of the structure . This parameter is important because the seismic action torque is equal to the moment of inertia of the structure multiplied by the torsional acceleration of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the response of a six-storey asymmetric building demonstrated the application of the proposed procedure, and the results are compared with the exact response at both edges computed from the integration of the motion equations of the isolated structure. Li et al (2007) focused their studies on the torsional acceleration of the structure θ¨s. This parameter is important because the seismic action torque is equal to the moment of inertia of the structure multiplied by the torsional acceleration of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the effects of mass eccentricity (CM) causes more torsional amplifications relative to stiffness eccentricity (CS) (Tena-Colunga and Escamilla-Cruz 2007). Li et al (2007) developed a method to study the torsionally coupled seismic responses of base-isolated structures. Hence, three formulas for different types of soil were proposed employing the torsional structure parameters such as eccentricities, the radius of gyration of the isolator and superstructure, uncoupled torsionlateral frequency ratio in the superstructure as well as lateral acceleration of the structure.…”
mentioning
confidence: 99%